Innate Lymphoid Cells in Response to Intracellular Pathogens: Protection Versus Immunopathology - Korchagina, Anna A.; Koroleva, Ekaterina; Tumanov, Alexei V. (Frontiers in Cellular and Infection Microbiology, 2021)
Innate lymphoid cells (ILCs) are a heterogeneous group of cytokine-producing lymphocytes which are predominantly located at mucosal barrier surfaces, such as skin, lungs, and gastrointestinal tract. ILCs contribute to tissue homeostasis, regulate microbiota-derived signals, and protect against mucosal pathogens. ILCs are classified into five major groups by their developmental origin and distinct cytokine production. A recently emerged intriguing feature of ILCs is their ability to alter their phenotype and function in response to changing local environmental cues such as pathogen invasion. Once the pathogen crosses host barriers, ILCs quickly activate cytokine production to limit the spread of the pathogen. However, the dysregulated ILC responses can lead to tissue inflammation and damage. Furthermore, the interplay between ILCs and other immune cell types shapes the outcome of the immune response. Recent studies highlighted the important role of ILCs for host defense against intracellular pathogens. Here, we review recent advances in understanding the mechanisms controlling protective and pathogenic ILC responses to intracellular pathogens. This knowledge can help develop new ILC-targeted strategies to control infectious diseases and immunopathology.